Influence of Rewards and Punishments on the Motivation to Learn Arabic Language in Class X of Al-Munawir Krapyak Vocational High School - Majid, Muhammad Kamil; Wijaya, Tahir; Qadhafi, Muhammad; Soufghalem, Aoumeur (Yayasan Azhar Amanaa Yogyakarta, 2023)
Rewards are given to motivate someone because there is an assumption that by giving gifts for good behavior and work results, he will maintain a good attitude and work more optimally, especially if the prize given is a tempting prize. Conversely, punishment is given to motivate someone not to make a mistake in carrying out something This study aims to determine the effect of Reward and Punishment on class X students at SMK al-Munawwir Krapyak. This study used a quantitative approach, with a sample of 24 students in class X at SMK al-Munawwir Krapyak. The results showed that: reward had a positive and significant effect on the motivation to learn Arabic in class X students at SMK al-Munawwir Krapyak, punishment had a positive and significant effect on motivation to learn Arabic in class X students at SMK al-Munawwir Krapyak.